Tax Changes and Phase Diagrams for an Overlapping Generations Model - Laitner, John (Journal of Political Economy, 1990)
The literature evaluating tax changes within an intertemporal general equilibrium framework subdivides into representative agent and overlapping generations formulations. Papers in the former class have developed techniques analogous to those routine for static analyses. I show that the same general approach works for the overlapping generations model. The context is the system from Auerbach and Kotlikoff's Dynamic Fiscal Policy. The proposed methodology allows one to examine stability and determinancy issues for the model, it deals precisely with small policy changes, and it can easily handle bundles of changes. I present comparative static results for comparison with existing work.